2017
DOI: 10.1038/s41598-017-06663-5
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state brain connectivity changes in obese women after Roux-en-Y gastric bypass surgery: A longitudinal study

Abstract: Bariatric surgery is an effective method to rapidly induce weight loss in severely obese people, however its impact on brain functional connectivity after longer periods of follow-up is yet to be assessed. We investigated changes in connectivity in 16 severely obese women one month before, one month after and one year after Roux-en-Y gastric bypass surgery (RYGB). 12 lean controls were also enrolled. Resting-state fMRI was acquired for all participants following an overnight fast and after a 260 kcal load. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 56 publications
(57 reference statements)
1
37
1
Order By: Relevance
“…We found that FC between the DMN nodes with clusters in the DMN and paralimbic somatosensory regions was altered to such a degree that positive correlations pre surgery “switched” to become anticorrelated post surgery. Although reduced FC between DMN nodes and anterior middle temporal gyrus was reported in RYGB patients scanned at similar time points , to our knowledge, we are the first to identify anticorrelations in the DMN in SG patients 1 year post surgery. DMN connectivity has been associated with self‐awareness and introspection , and both DMN intranetwork correlations and DMN internetwork anticorrelations were proposed to be integral to consciousness .…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…We found that FC between the DMN nodes with clusters in the DMN and paralimbic somatosensory regions was altered to such a degree that positive correlations pre surgery “switched” to become anticorrelated post surgery. Although reduced FC between DMN nodes and anterior middle temporal gyrus was reported in RYGB patients scanned at similar time points , to our knowledge, we are the first to identify anticorrelations in the DMN in SG patients 1 year post surgery. DMN connectivity has been associated with self‐awareness and introspection , and both DMN intranetwork correlations and DMN internetwork anticorrelations were proposed to be integral to consciousness .…”
Section: Discussionmentioning
confidence: 45%
“…The post‐RYGB group showed similar FC strength within the DMN compared with a lean group, suggesting weight loss following RYGB and/or the surgery itself normalized aberrant FC associated with obesity . In a recent longitudinal study, connectivity between the precuneus and anterior superior temporal gyrus decreased from before to 1 year after RYGB compared with no changes in individuals with lean BMI scanned at a parallel interval . Within the RYGB group, there was a reduction in FC strength between the PCC (a node in the DMN) with the anterior superior temporal gyrus and anterior temporal fusiform gyrus .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations